The Evolution of the Bío Bío Delta and the Coastal Plains of the Arauco Gulf, Bío Bío Region: the Holocene Sea-Level Curve of Chile - Isla, Federico Ignacio (2012)
Mid-Holocene highstands are characteristic of the Southern Hemisphere. The Chilean coast extends from 17°S to 56°S in a dominant microtidal regime; thus, it is an ideal place to test ages and altitudes of this highstand with minimal errors. However, coseismic events, the dynamic phenomena they triggered (tsunamis), and the behaviour of land in relation to the overriding of the South American Plate over the oceanic Nazca Plate, make it necessary to distinguish these effects from purely eustatic changes. To the south, the glacioisostatic uplift has been approximately measured. At 37°S, the Coronel coastal plain extends several kilometres inland. Its sediment availability has been related to the supplies of the Bío Bío River. From this beach-ridge plain, shell remains gave a radiocarbon age of 4370 ± 90 years before present (YBP), indicating a highstand not higher than 5 m. Further south, at the Carampangue coastal plain, southern coast of the Arauco Gulf, a radiocarbon age of 8010 ± 90 YBP marks the oldest age of this transgression. Some consequences of the earthquake and tsunami of February 27, 2010, are reported here. The radiocarbon ages of these plains permit completion of a Holocene sea-level curve. These Holocene sea-level data were compared to other regions of South America.